Comparative Exhaust-Gas Characteristics of Sugarcane Bagasse and Pineapple Waste Bioethanol Blends in a Fuel-Injected Motorcycle under a Common HHO-System Configuration - Calvin M. P. Sinaga; Wawan Purwanto; M. Yasep Setiawan; Ahmad Arif (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Agricultural waste-derived bioethanol offers a renewable gasoline-blending option for spark-ignition engines. This study compared sugarcane bagasse- and pineapple waste-derived bioethanol blends in a fuel-injected Honda BeAT motorcycle operated under a common HHO-system configuration. Five fuel formulations—E0, E5-SC, E10-SC, E5-PW, and E10-PW—were tested at 1500, 4000, and 7000 rpm. CO, HC, CO₂, and O₂ were measured using a four-gas analyzer, while λ and AFR were reported by the analyzer. Results are presented as means from three replicate runs. E10-SC recorded the lowest mean CO concentration at 4000 rpm and the lowest mean HC concentration at 7000 rpm, whereas E10-PW recorded the lowest mean CO concentration at 7000 rpm. The formulation rankings varied with engine speed and measured parameter. Because HHO was not tested independently, its specific contribution could not be determined.